Synthesis of Symmetrical Disulfides by an NIS/PPh3-Mediated Reductive Self-Coupling of Sulfonyl Hydrazides - Yadav, Ashvani; Gond, Amrit; Prasad, Virendra (Synlett, 2023)
The present study discloses an NIS/PPh3-mediated reductive self-coupling of arylsulfonyl hydrazides to prepare symmetric diaryl disulfides. This methodology has a broad functional-group tolerance and a high scalability. This strategy permits the introduction of sulfonyl hydrazides into the synthesis of symmetrical organic disulfides without the use of a catalyst or base, and symmetrical aromatic disulfides can be prepared in moderate to excellent isolated yields from inexpensive and readily available starting materials.
Keywords: disulfides; arylsulfonyl hydrazides; aryl disulfides; reductive coupling